Factors affecting risk perception of COVID-19: differences by age and gender - Kang, Sungwook; You, Chang Hoon; Kwon, Young Dae (Frontiers in Public Health, 2025)
IntroductionAddressing emerging infectious diseases is a major task in public health. This study investigated the factors influencing the perception of risk related to COVID-19.MethodsThis study analyzed data from the 2020 Social Survey conducted nationwide in South Korea, targeting 34,909 individuals aged 13 years and older. Using an ordered logit regression model, we examined the relationship between COVID-19 risk perception and its predictors across age groups (20–44 years, 45–64 years, 65 years and older) and gender groups. The predictors included in the analysis model were demographic factors, socioeconomic factors, health and quality of life factors, levels of social trust, and climate change factors.ResultsThe results demonstrated that COVID-19 risk perception was higher among older individuals and women compared with men. In the young population group (20–44 years), mental stress was related to COVID-19 risk perception, but this was not observed in other population groups. In the older adult population group (65 years and older), education level was related to COVID-19 risk perception, whereas this was not observed in the young population group. In the male group, economic variables such as income and employment status were related to COVID-19 risk perception, whereas in women, family-related variables such as marital status and housing type were related. In most subgroup analyses, lower income levels or lower life satisfaction were associated with higher COVID-19 risk perception.DiscussionThe findings of this study suggest that health authorities need to tailor their responses to COVID-19 risk perception based on different populations and social groups. For the older adult population with a high-risk perception, it is necessary to provide reliable information to reduce anxiety caused by excessive risk perception. For the young population, proactive responses from health authorities regarding mental health are needed.